Transcriptomic characterization of two major Fusarium resistance quantitative trait loci (QTLs), Fhb1 and Qfhs.ifa‐5A, identifies novel candidate genes. (6th June 2013) - Schweiger, Wolfgang; Steiner, Barbara; Ametz, Christian; Siegwart, Gerald; Wiesenberger, Gerlinde; Berthiller, Franz; Lemmens, Marc; Jia, Haiyan; Adam, Gerhard; Muehlbauer, Gary J.; Kreil, David P.; Buerstmayr, Hermann
Summary Fusarium head blight, caused by Fusarium graminearum, is a devastating disease of wheat. We developed near‐isogenic lines (NILs) differing in the two strongest known F. graminearum resistance quantitative trait loci (QTLs), Qfhs.ndsu‐3BS (also known as resistance gene Fhb1) and Qfhs.ifa‐5A, which are located on the short arm of chromosome 3B and on chromosome 5A, respectively. These NILs showing different levels of resistance were used to identify transcripts that are changed significantly in a QTL‐specific manner in response to the pathogen and between mock‐inoculated samples. After inoculation with F. graminearum spores, 16 transcripts showed a significantly different response for Fhb1 and 352 for Qfhs.ifa‐5A. Notably, we identified a lipid transfer protein which is constitutively at least 50‐fold more abundant in plants carrying the resistant allele of Qfhs.ifa‐5A. In addition to this candidate gene associated with Qfhs.ifa‐5A, we identified a uridine diphosphate (UDP)‐glycosyltransferase gene, designated TaUGT12887, exhibiting a positive difference in response to the pathogen in lines harbouring both QTLs relative to lines carrying only the Qfhs.ifa‐5A resistance allele, suggesting Fhb1 dependence of this transcript. Yet, this dependence was observed only in the NIL with already higher basal resistance. The complete cDNA of TaUGT12887 was reconstituted from available wheat genomic sequences, and a synthetic recoded gene was expressed in a toxin‐sensitive strain of Saccharomyces cerevisiae. This gene conferred deoxynivalenol resistance, albeit much weaker than that observed with the previously characterized barley HvUGT13248.